Insulation Thickness versus Dynamic Thermal Parameters of External Walls with Regard to the Thermal Stability - Ponechal, Radoslav; Staffenova, Daniela (Communications - Scientific letters of the University of Zilina, 2017)
It appears that the walls, insulated according to the new requirements for thermal resistance, can contribute to thermal stability. This is advantageous not only for the thermal comfort during the summer but in the cases of the intermittent heating, or overheating, as well. This article evaluates some alternatives of insulated and uninsulated external walls. The phase time shift of the indoor surface temperature with respect to the outdoor surface, together with the periodic penetration depth of indoor surface temperature, are considered in this analysis. Analyzing subsurface temperature courses we evaluate the ability of construction to accumulate heat gains, which can arise during the day.